2014
DOI: 10.1016/s1995-7645(14)60025-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of pAkt and HIF-1 α on ischemia rats

Abstract: pAkt, HIF-1 α have neuroprotective effect on ischemia rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…The observed upregulation of the antiapoptotic protein kinase Bα (Akt-α) was apparently aimed to cell protection against strokeinduced apoptosis. These data correlate with the increased phosphorylation of Akt and rise in the Akt mRNA level in the ischemic brain of rats [23,24]. Downregulation of proapoptotic kinase GSK-3, which is negatively controlled by protein kinase B/Akt, could be also neuroprotective.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The observed upregulation of the antiapoptotic protein kinase Bα (Akt-α) was apparently aimed to cell protection against strokeinduced apoptosis. These data correlate with the increased phosphorylation of Akt and rise in the Akt mRNA level in the ischemic brain of rats [23,24]. Downregulation of proapoptotic kinase GSK-3, which is negatively controlled by protein kinase B/Akt, could be also neuroprotective.…”
Section: Discussionsupporting
confidence: 54%
“…β-Amyloid is produced from amyloid precursor protein (APP) by TMP21, a member of the presenilin complex [42]. The observed accumulation of β-amyloid peptide (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) in penumbra could be also neurotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…And, it might participate in the regulations of angiogenesis, glucose metabolism, anti-apoptosis, and cellular survival during hypoxia. [1718] It could also upregulate such genes as glucose transporters, erythropoietin, and vascular endothelial growth factor. [19] The underlying mechanisms will be elucidated by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of residue Ser-473 is required for Akt activity [15]. It has been shown that Akt phosphorylation at Ser-473 and Thr-308 has an obvious relationship with brain ischemia and plays an important neuroprotective role [16]. The proline-rich Akt substrate of 40 kDa (PRAS40) protein is a substrate of the protein kinase Akt and can reduce brain injury [17].…”
Section: Introductionmentioning
confidence: 99%